Backscratching in Hierarchical Organizations - Valeria Maggian; Natalia Montinari; Antonio Nicolò (Lund University, School of Economics and Management, Department of Economics, 2015)
In this paper we investigate the role of reciprocity in sustaining the emergence of implicit collusive agreements in hierarchical organizations. We conduct a laboratory experiment in which an agent hires, on behalf of the principal, one worker out of two candidates. The two candidates differ in their ability and, once employed, the worker chooses a level of non-contractible effort to exert in two tasks: one benefits the organization (that is both the principal and the agent) while the other one is less profitable, only benefits the agent and provides him with higher earnings. We provide evidence that: i) low ability workers are more likely to exert effort in the task that is exclusively beneficial to the agent; ii) as a consequence, agents distort the hiring process in favor of the low ability workers and iii) sharing a small part of the organization's profits with the workers alleviates their effort distortion.
Keywords: C91; J50; L14; M52; 330; Conflict of Interest; Effort Distortion; Profit Sharing; and Reciprocity